The psychological predictors of activity of IT-professional sinconditions of organizational transition to remote work - Maksymenko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article is devoted to the actual problem of psychological support of the transition of office workers to remote work. The purpose of the article is the definition of psychological and socio-demographic determinants of the activities of managers in the context of junior personnel transfer to virtual / home office. This problem is considered on the example of IT-professionals (n = 182) from four countries of Central and Eastern Europe. It is proved that the basic dispositional features that contribute to the realization of the activity potential are conscientiousness and openness to experience. Among the value orientations such predictors are the orientations towards competent and tolerant leadership. Another important thing is the value orientations of altruism and independence. The author makes conclusion that duing formation of uncertainty in their actions, individual personal traits play a great role, especially such traits as: ease of occurrence of negative emotions, individualism, preference for independence, disorganization, spontaneity, low level of purposeful behavior. Therefore, an orientation towards social support makes it difficult to implement an orientation towards quality in an activity and reinforces the lack of self-confidence feelings. It was revealed that under conditions of restructuration dispositional factors begin to play a major role, and the degree of value regulation decreases. In addition, the author suggests that a low level of integrity promotes creativity. This can be explained by the fact that an individual, who has such low level, remains open for longer to various possibilities of thought and action. The results of the analysis of the research data indicate that value orientations act as a kind of basis. They head the realization of the personal characteristics of a specialist in professional activity and they are important qualities in everyday life. In the article it is determined that the desire for success decreases in the specialists who get older, and the value orientations for support and leadership contribute to this aspiration. The author has shown that openness of experience, combined with tolerant leadership, is a prerequisite for determination in promoting organizational change.
Keywords: IT professionals, psychological predictors, remote work, managerial potential, personality traits, value orientations.